Blackout - Wells, Robison E. (HarperTeen, 2013)
"A mysterious virus is spreading through America, infecting teenagers with incredible powers--and a group of four teens are about to find their lives intertwined in a web of danger and catastrophic destruction"--Provided by publisher.